The Association Between Pregnancy-Induced Hypertension and Neonatal Cerebral Metabolism, Hemodynamics, and Brain Injury as Determined by Physiological Imaging - Qi, Ying; Lin, Zixuan; Lu, Hanzhang; Zhao, Pengfei; Hou, Yang; Mao, Jian (Frontiers in Physiology, 2022)
Pregnancy-induced hypertension (PIH) is common and may affect maternal and children’s healthcare. However, the neurobiological status of neonates born from mothers with PIH has yet to be elucidated. The present study employed physiological imaging to investigate the association between maternal PIH and a number of neonatal health parameters, including cerebral metabolism, hemodynamics, and pathophysiological vulnerabilities. Following the acquisition of ethical approval, we recruited 16 neonates with maternal PIH and 22 normal neonates (non-PIH) as controls. All neonates underwent magnetic resonance imaging (MRI) of the brain. Phase-contrast (PC) MRI and T2-relaxation-under-spin-tagging (TRUST) MRI were performed to determine global cerebral blood flow, oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO2). These physiological parameters were then compared between PIH neonates and controls. Linear regression analysis was performed to investigate the associations between maternal PIH and each of the physiological parameters. Receiver operating characteristic curves (ROCs) were used to determine whether maternal systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) which could facilitate the diagnosis of neonatal brain injuries. PIH neonates showed significantly lower OEF (25.5±8.8% vs. 32.6±7.3%, P=0.01) and CMRO2 (29.7±9.4 μmol/100 g/min vs. 40.9±15.0 μmol/100 g/min, P=0.01) compared to the controls. Maternal blood pressure levels (PIH or non-PIH groups, each one standard deviation (SD) increase in SBP, DBP, and MAP, respectively) were negatively associated with OEF (regression coefficient (β)=-7.9, P=0.007; β=-4.2, P=0.004; β=-3.6, P=0.02; β=-4.0, P=0.008, respectively). Furthermore, each one SD increase in maternal DBP and MAP was negatively associated with CMRO2 (β=-4.7, P=0.03; β=-4.4, P=0.04, respectively). The areas under the curves (AUCs) with 95% confidence intervals (CIs) for maternal SBP, DBP, and MAP were 0.90 (0.80–0.97), 0.85 (0.73–0.97), and 0.89 (0.76–0.99), respectively. The AUC values for maternal SBP, DBP, and MAP indicated good diagnostic ability for identifying neonatal brain injuries. The present study demonstrated that maternal PIH may be associated with a lower oxygen extraction and lower cerebral metabolism in neonates.